KIPRAH SAKDIAH DALAM KANCAH MUSIK POP DAERAH GAYO - Raudhatul Jannah; G. R. Lono Lastoro Simatupang; Wiwik Sushartami (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2019)
Sakdiah is a woman from Gayo, Aceh. She has pursued her career as a pop singer in the land of Sharia Aceh, among the Gayo ethnic group that practice a patriarchal system. Pop music is mostly dominated by men and this situation determines the position of women in the world of music. Using the methods from ethnomusicology, this research looks at Sakdiah’s position in the Gayo pop music and her journey in the world of music. The result of this research proves that Sakdiah is one of the most productive singers releasing albums. She has chosen to appear on stage as a solo singer. Her success is inseparable from music agents and producers.